Antifungal activity of papaya leaf extract against Fusarium oxysporum in red chili (Capsicum annuum L.) - Desi Sri Pasca Sari; Lita Nasution; Nico Syahputra Sebayang; Asmawati; Dali (Talenta Publisher, 2026)
Chili pepper (Capsicum annuum L.) is a high-value horticultural commodity in Indonesia; however, its production is frequently constrained by Fusarium wilt caused by Fusarium oxysporum, a destructive soil-borne pathogen capable of inducing substantial yield losses. The intensive use of synthetic fungicides for disease management poses environmental risks and may disrupt soil microbial balance, thereby necessitating the development of sustainable and eco-friendly control strategies. This study aimed to assess the antifungal efficacy of papaya (Carica papaya L.) leaf extract against F. oxysporum under in vitro conditions. The experiment was conducted using a Completely Randomized Design (CRD) with five extract concentration treatments and three replications. Antifungal activity was evaluated based on the inhibition of fungal mycelial growth on Potato Dextrose Agar (PDA) medium. The results indicated that papaya leaf extract significantly suppressed the radial growth of F. oxysporum, with inhibitory effects increasing proportionally to extract concentration. Statistical analysis revealed a highly significant effect of treatment concentration on fungal growth inhibition. The highest antifungal activity was observed at a concentration of 8.5 ml, suggesting optimal suppression of mycelial development. These findings demonstrate that papaya leaf extract possesses strong antifungal properties and has considerable potential as a plant-based biocontrol agent for the management of Fusarium wilt in chili pepper cultivation.